Designing Mix-Use Waterfront in Kampung Badur - Dwira Nirfalini Aulia; Regina Novita (International Journal of Architecture and Urbanism, 2018)
Currently, the population growth is growing very rapidly resulting in rapid growth of the needs of settlements. The population growth that is not proportional to the availability of land and the income level of the lower middle class resulted in the emergence of illegal settlements and slums and are on land that is inconsistent with the city spatial plan for example on the edge of the river. This condition causes the decreasing quality of life of the people, especially in urban areas, destroying the environment and the spatial arrangement of the city. Medan city is one of the cities that there are many slums. One of the slums in the city of Medan is Kampung Badur located in Hamdan Village Medan Maimun District. The condition of the slums and the low economic level and the location of Kampung Badur located in the city center became the main problem in this area. Therefore, a solution is needed to solve problems in the area by making Kampung Badur an area that provides decent occupancy for occupancy and facilities that could be enjoyed together. The solution to this problem is to re-arrange Kampung Badur and develop potentials in the area. For example, Kampung Badur area which is right on the edge of the river becomes a potential in the design. So that the solution that can be applied is to develop Kampung Badur into Mix-Use Waterfront with a mix-use concept such as residential, public facilities and public open space to be enjoyed by residents Kampung Badur itself and by the people of Medan City.